Plane Contact of a Cylindrical Opening Stiffened by a Thin Shell - Bardzokas, D.; Exadaktylos, G.E. (Engineering Transactions, 1995)
In the present paper the plane contact problem is considered, concerning a circular cylindrical hole stiffened by an elastic circular cylindrical tube (stringer) around its perimeter in a biaxial state of stresses at infinity. For the formulation of the interface conditions, the elastic stringer is considered to behave as a thin shell, and its outer diameter, prior to its insertion into the hole, may be equal or greater than the radius of the hole by a small value of the order of the (infinitesimal) elastic displacements. The solution of this mixed boundary value problem in plane strain conditions is found by numerical integration of a system of a complex singular, and complex regular integral equation describing the boundary and interface conditions of the problem, respectively. The classical method of Kolosov-Muskhelishvili complex potentials ɸo(z), Ѱo(z), in combination with the theory of singular integral equations, is considered in this paper in order to obtain the solution of the mixed boundary value problem stated above.